Narratives From Women Rural Workers: The Construction of Subalternity, Hierarchized Spaces and Colonial Domination - Dornela, Fernanda Junia; Medeiros, Cintia Rodrigues de Oliveira (Organizações & Sociedade, 2021)
In this research, our aim is to analyze how gender relations are manifested in the narratives of women rural workers, in coffee farming in the Cerrado Mineiro Region, in a post-colonial perspective. It is a qualitative research, the empirical material of which consists of narrative interviews conducted with 14 rural coffee workers in the municipalities of Patrocínio, Carmo do Paranaíba and Monte Carmelo, in the state of Minas Gerais. The empirical material was submitted to the thematic analysis technique. The results suggest that gender relations are expressed through inheritances of colonialism, which constitute the themes identified: (1) constructed subordination; (2) hierarchical spaces; and (3) colonial domination.